Medical students' knowledge and perception toward family planning services: A preliminary intervention study - Htay, Mila Nu Nu (J Educ Health Promot, 2018)
INTRODUCTION: Family planning and contraception is the effective strategy to reduce maternal mortality, child mortality, abortion, and unwanted pregnancies. Since the medical students are the future doctors, it is important to have proper knowledge and training on family planning services. This study aimed to explore the effect of teaching-learning process at maternal and child health (MCH) clinics on the students' knowledge, perceptions toward contraception methods, and family planning counselling. METHODS: This quasi-experimental study was conducted in the private medical institution in Malaysia. The same questionnaire was used to administer twice, before and after the posting. Moreover, a qualitative question on the issues related to family planning and contraception utilizations in Malaysia was added to the after posting survey. The quantitative data were analyzed using IBM SPSS (version 20) and qualitative data by RQDA software. RESULTS: A total of 146 participants were recruited in this study. Knowledge on contraception method before posting was 5.11 (standard deviation [SD] ±1.36) and after posting was 6.35 (SD ± 1.38) (P < 0.001). Thematic analysis of the students' answer revealed four salient themes, which were as follows: (1) cultural barrier, (2) misconception, (3) inadequate knowledge, and (4) improvement for the health-care services. CONCLUSIONS: The teaching-learning process at the MCH posting has an influence on their perception and upgraded their knowledge. It also reflects the role of primary health-care clinics on medical students' clinical exposure and training on family planning services during their postings.